THE ROLE OF TRAINING AND CERTIFICATION IN IMPROVING THE COMPETENCE OF ISLAMIC RELIGIOUS TEACHERS - Nurhaizan Sembiring (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research aims to analyze the role of training and certification in improving the competence of Islamic teachers, both from pedagogic, professional, and work attitude aspects. The research uses a qualitative approach with a descriptive method. Data was collected through in-depth interviews, observations, and documentation of Islamic teachers who have participated in training and certification under the guidance of the Ministry of Religion. The results of the study show that training plays an important role in improving teachers' ability to design learning, master teaching materials, and utilize digital technology in the teaching and learning process. Meanwhile, certification provides professional recognition that encourages a teacher's motivation, responsibility, and commitment to their profession. The two programs complement each other in forming Islamic teachers who are competent and adaptive to educational changes. However, several obstacles were found such as time limitations, inequality of access to training, and lack of post-training assistance. Therefore, a training and certification policy that is sustainable, needs-based, and oriented towards improving the quality of learning is needed.